Customer satisfaction and international business: A multidisciplinary review and avenues for research - Hult, G. Tomas M.; Morgeson III, Forrest V.; Sharma, Udit; Fornell, Claes (Journal of International Business Studies, 2022)
We systematically review the literature on customer satisfaction, partitioning the literature into three generations of thought and focus, with the most recent, third generation, heavily emphasizing international business phenomena. Following a brief, stage-setting review of the first two generations – which address, respectively, the psychological underpinnings of the satisfaction concept, its antecedents, and consequences (first-generation), and the relationship between customer satisfaction, its strategic firm drivers, and firm financial performance outcomes, as well as moderators and mediators of those drivers and outcomes (second-generation) – we primarily focus on the third-generation international studies that have emerged over approximately the last 20 years. These third-generation studies have predominantly investigated the customer satisfaction concept as it is applied cross- and multi-nationally in diverse international market contexts but, due in large part to the cross-disciplinary nature of this research, this literature is fragmented and disjointed. Following a review and synthesis of the third-generation satisfaction literature, connecting it to and differentiating it from the first two generations and integrating its main themes and most significant findings, we identify enduring gaps and unanswered research questions. Of particular note is the dearth of studies examining cross- and multinational moderators of both the strategic firm drivers of satisfaction and the satisfaction–firm performance relationship. We conclude with avenues for future research that can generate important IB-related customer satisfaction knowledge with the potential to provide enormous value to international researchers and managers.